Tinjauan Yuridis Perkawinan Suku Anak Dalam di Jambi Berdasarkan Hukum Adat dan UU Perkawinan - Winsherly Tan; Bulan Ayu Sari (Journal of Judicial Review, 2018)
The Act No. 1 year 1974 concerning Marriage was born as government efforts to do legal unification for resolve legal uncertainty about marriage problems. One of which is indigenous people of Indonesia is Suku Anak Dalam who still implement their customary marriage law and rule out Act No. 1 year 1974 concerning Marriage has been positive law in Indonesia. Research methodology used is law research method juridical normative, the data that used is in the form of secondary data, which consist of both primary and secondary legal materials. The author collecting the data by doing library research. Once all the data is collected, the data then processed and analyzed. The qualitative method was used to group the data point by the studied aspects. Further conclusions drawn related to this study, then describe descriptively. Based on the result of research that has been done, there are some significant differences in Suku Anak Dalam customary marriage law with legal provisions on Act No. 1 year 1974 concerning Marriage. Then, Suku Anak Dalam customary marriage law although recognized based on Indonesia laws, however communities that runned customary law also must implement Act No. 1 year 1974 concerning Marriage. Need a law harmonization between customary law especially Suku Anak Dalam customary law with Act No. 1 year 1974 concerning Marriage.